The influence of parameters on the evolution of the friction surfacing method-a review - Ozcan, Mehmet Erbil (Korean Soc Mechanical Engineers, 2022)
Friction surfacing is a coating technology based on the accumulation of two metals with the same or different properties by transforming into a viscous structure without the need for an external heat source. The frictional surfacing process, which is based on the principle of coating by melting method by reaching the desired temperature with the contact of the consumable rod rotating around its axis, is used to bring the desired properties of the material together. The friction surfacing method, which can be made with many material pairs, requires a separate expertise in terms of achieving the desired temperature and adhesion of the materials to each other when made with the steel material pair. In this study, when the friction surfacing process is made with other materials and especially steel material combinations, the parameters used and the properties examined are investigated and the fundamentals of friction surfacing and recent developments are examined in the light of the literature. The advantages and disadvantages of the method, its usage areas and the theoretical and experimental studies for the people working on new coating methods have been brought together and a different perspective by examining the factors affecting the coating method one by one has been revealed with this study.
Keywords: Friction surfacing; Coating; Steel; Aluminum; Composite